Intestinal transport of sophocarpine across the Caco‐2 cell monolayer model and quantification by LC/MS. (June 2014) - Sun, Sen; Zhang, Hai; Sun, Fengfeng; Zhao, Liang; Zhong, Yanqiang; Chai, Yifeng; Zhang, Guoqing
ABSTRACT Sophocarpine is a biologically active component obtained from the foxtail‐like sophora herb and seed that is often orally administered for the treatment of cancer and chronic bronchial asthma. The aim of this study was to develop a rapid and specific LC/MS method for the determination of sophocarpine and to explore its transcellular transport mechanism across the Caco‐2 (the human colon adenocarcia cell lines) monolayer cell transwell model. Caco‐2 cells were seeded on permeable polycarbonate membranes and incubated for 21 days. Before the experiment, the trans‐epithelial electric resistance, integrity and alkaline phosphatase activity of the Caco‐2 monolayers were verified and used in subsequent experiments. In the Caco‐2 model constructed, many influencing factors were investigated, including time, concentration, pH and different protein inhibitors. The results suggested that sophocarpine was transported mainly by passive diffusion. The flux of sophocarpine was time‐ and concentration‐dependent, and the pH also had an effect on its transportation. The PappBA was higher than PappAB, indicating that a polarized transport might exist for sophocarpine. MK‐571 and reserpine, inhibitors of the multidrug resistance associated protein 2 and the breast cancer resistance protein, decreased the efflux of sophocarpine, while verapamil had no effect on its transport. These results revealed that sophocarpine is absorbed mainly by passive diffusion, and that a carrier‐mediated mechanism is also involved in the transport of sophocarpine. Copyright © 2014 John Wiley & Sons, Ltd.